Carotenoids and antioxidant capacities from Canarium odontophyllum Miq. fruit. - Prasad, K. Nagendra; Chew, Lye Yee; Khoo, H.E.; Yang, Bao; Azlan, Azrina; Ismail, Amin (Elsevier Science Limited, 2011)
Carotenoids were isolated and identified from peel, pulp and seed fractions of Canarium odontophyllum Miq., and their antioxidant capacities were evaluated. all-trans-β-carotene was present in a large amount in peel (69.5 ± 1.0 mg/kg), followed by pulp (31.1 ± 0.76 mg/kg) and seed (15.1 ± 3.0 mg/kg). Additionally, 15-cis-β-carotene, 9-cis-β-carotene and 13-cis-β-carotenes were also major contributors to carotenoid contents in peel, pulp and seed fractions. Pulp exhibited excellent β-carotene bleaching activity, significantly higher than peel and seed; high 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging activity, whereas peel exhibited significantly higher scavenging activity of 2,2’-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) radicals. All the extracts exhibited good inhibitory effect against hydrogen peroxide-induced haemoglobin oxidation, ranging from 45.3 to 59.7%. This is the first report about carotenoids and antioxidant capacities from C. odontophyllum fruit, and indicates that this fruit can be explored and promoted as a potential source of natural antioxidants.